Kedudukan Keterangan Korban Pada Agenda Pembuktian Yang Tidak Dapat Hadir Dipersidangan - Muchammad Huzaifi (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to analyze the importance of the position of the victim whose statement will be heard in order to shed light on a crime. The type of research that the writer uses is normative legal research. The type of research in thesis writing is about the blurring of norms contained in Article 160 paragraph (1) letter b. As for this study, researchers used several approaches. statute approach and conceptual approach. The results of this study are that the testimony of the victim given can be of evidentiary value even though it depends on other evidence, which is different from the evidence provided by witnesses who are bound by the principle one witness no witness pursuant to Article 186 paragraph (6) of the Criminal Procedure Code.